2018
DOI: 10.1002/dmrr.3100
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes pharmacotherapy and effects on the musculoskeletal system

Abstract: Summary Persons with type 1 or type 2 diabetes have a significantly higher fracture risk than age‐matched persons without diabetes, attributed to disease‐specific deficits in the microarchitecture and material properties of bone tissue. Therefore, independent effects of diabetes drugs on skeletal integrity are vitally important. Studies of incretin‐based therapies have shown divergent effects of different agents on fracture risk, including detrimental, beneficial, and neutral effects. The sulfonylurea class of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
67
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(69 citation statements)
references
References 536 publications
(983 reference statements)
0
67
1
1
Order By: Relevance
“…Ex-4 and sitaglitin (DPP4 inhibitor) are known to improve kidney function by attenuating inflammation in chronic or diabetic kidney disease models. 17,72 Therefore, it is unclear whether the beneficial effect of Ex-4 is due to its role in improving kidney function, its direct effect on muscle, or both in the current study. Further studies are needed to clarify this.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Ex-4 and sitaglitin (DPP4 inhibitor) are known to improve kidney function by attenuating inflammation in chronic or diabetic kidney disease models. 17,72 Therefore, it is unclear whether the beneficial effect of Ex-4 is due to its role in improving kidney function, its direct effect on muscle, or both in the current study. Further studies are needed to clarify this.…”
Section: Discussionmentioning
confidence: 80%
“…Similar to the observations in Dex‐treated mice, Ex‐4 significantly increased total muscle mass, CSA of the TA muscle, and muscle function in CKD mice. Ex‐4 and sitaglitin (DPP4 inhibitor) are known to improve kidney function by attenuating inflammation in chronic or diabetic kidney disease models . Therefore, it is unclear whether the beneficial effect of Ex‐4 is due to its role in improving kidney function, its direct effect on muscle, or both in the current study.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Research has demonstrated roles for magnesium, calcium and vitamin D in promoting wound healing, with clinical trial evidence of enhanced diabetic foot ulcer healing with both magnesium and vitamin D supplementation [27][28][29]. Canagliflozin administration led to an increase of urine calcium excretion and magnesium wasting in animal models, and a decrease in 1,25(OH) 2 -vitamin D in hospitalised patients [30]. Further research is needed in humans to determine whether these effects on calcium, magnesium and vitamin D metabolism are specific to canagliflozin or a general characteristic of SGLT2 inhibitors.…”
Section: Potential Mechanismsmentioning
confidence: 99%
“…The prevalence of type 2 diabetes is increasing worldwide, and it is pathologically involved in accelerating the loss of muscle mass and strength. Muscle atrophy is a high‐risk factor for physical disability and mortality; therefore there is an urgent need to develop effective strategies to prevent and treat diabetes‐related muscle atrophy, including sarcopenia.…”
Section: Introductionmentioning
confidence: 99%